2014
DOI: 10.1515/cclm-2013-0885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of INK4A promoter methylation using pyrosequencing and circulating cell-free DNA from patients with hepatocellular carcinoma

Abstract: Background Hyper-methylation of CpG dinucleotides in the promoter region of inhibitor of cyclin-dependent kinase 4A (INK4A) has been reported in 60%–80% of hepatocellular carcinoma (HCC). As INK4A promoter hypermethylation event occurs early in HCC progression, the quantification of INK4A promoter methylation in blood sample may represent a useful biomarker for non-invasive diagnosis and prediction of response to therapy. Methods We examined INK4A promoter methylation using circulating cell-free DNA (ccfDNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 43 publications
(62 reference statements)
0
22
0
2
Order By: Relevance
“…MT1M and MT1G methylation were detected in HCC patients´ serum with a significantly higher frequency compared to patients with CHB or the healthy control group [50]. Occurring early in liver tumor progression with higher levels in HCC patients, INK4A promoter hyper-methylation also showed the potential as a biomarker [45].…”
Section: Gene Methylation Alterationsmentioning
confidence: 91%
“…MT1M and MT1G methylation were detected in HCC patients´ serum with a significantly higher frequency compared to patients with CHB or the healthy control group [50]. Occurring early in liver tumor progression with higher levels in HCC patients, INK4A promoter hyper-methylation also showed the potential as a biomarker [45].…”
Section: Gene Methylation Alterationsmentioning
confidence: 91%
“…67 Results for this single candidate have been mixed. 71,72 Up to 90% of HCC tissues have DNA extracts with hypermethylation of the RASSF1A promoter, 73 were reflected in high frequency of hypermethylation by methylation-specific PCR of cfDNA. [74][75][76][77] Other single methylation marker candidate studies have shown high detection of HCC.…”
Section: Aberrant Ctdna Methylationmentioning
confidence: 99%
“…High incidence of p16INK4a promoter hypermethylation in ctDNA with significant decrease in postoperative blood samples was shown to be a useful marker in the detection and monitoring of HCC (Wong et al 2003). Correspondingly, Huang et al demonstrated higher levels of methylated p16INK4a in circulating cfDNA of 66 HCC serum samples versus 43 benign chronic liver diseases (Huang et al 2014). Further common tumor suppressing and cell cycle regulation-related genes with promoter hypermethylation are the adenomatous polyposis coli (APC) on chromosome 5q21 and the Ras association domain family protein 1A (RASSF1A) genes on chromosome 3p21.3 with high frequency of promoter hypermethylation in tumor and blood samples of HCC patients (Hu et al 2010;Huang et al 2011;Yeo et al 2005).…”
Section: Methylation Alterations Of Ctdna In Hccmentioning
confidence: 99%